Associations Of Betatrophin Levels With Fasting Blood Glucose In Obese Females - Pradika Gita Baskara; Lilik Herawati; Purwo Sri Rezeki (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This study aims to analyze the correlation between the levels of betatrophin and fasting blood glucose (FBG) in obese females. This study used a cross sectional study method of 26 obese female aged 18-23 years old, body mass index (BMI) 25-35 kg/m2 and body fat percentage (PBF) above 30%. Betatrophin levels were measured by ELISA method, while FBG measurements used ACCU-CHEK® Performance. The data analysis techniques used the Pearson Correlation test with the Statistical Package for Social Sciences (SPSS). The results obtained the average of betatrophin level (165.707 ± 96.124) pg / mL and the average of FBG (90.576 ± 7.094) g / dL (p = 0.021). Based on the results of the study it can be concluded that there is a correlation between levels of betatrophin and FBG in obese adolescent girls with a negative correlation direction